PENYUSUNAN SISTEM INFORMASI GEOGRAFIS RUANG PUBLIK BERBASIS WEBGIS MEMANFAATKAN PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS DI KOTA YOGYAKARTA - , BAKHTIAR ARIF M, Barandi Sapta Widartono, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aims of the research are to map public space using Quickbird satellite imagery and create webgis of public space at Yogyakarta municipality. The primary data source was obtained by interpretation of quickbird sattelite imagery and field surveying. Research methodology used for mapping public space were the combination between visual interpretation technique and field survey. Visual interpretation applied to collect the location of public space typology quickly. Validation of interpretation done by field surveying. Field survey also to obtain public space added information and findings. Data of public space defined by validated interpretation and field survey findings. Webgis of public space is a map that disseminated by web which public space as the main information. Processes in order to create webgis prototype of public space are data classification, database creation, generalization, symbolization, map service creation and interface design. 810.012,69 Research results showed that public space mapped by quickbird satellite imagery has 65,25% of mapping accuracy, which 14 types of public space typology. Located on 901 locations and m2 of total width. Webgis of public space arraged which public space as the main information. It provides features to make end users obtain the information on system easily. The features are coordinate feature, scale feature, navigation, menu, geocode, theme selection, identify and inset.